2021
DOI: 10.30773/pi.2020.0438
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Neural Effect of Electroconvulsive Therapy in Patients with Schizophrenia: Hippocampus and Insula as the Key Regions of Modulation

Abstract: Objective Electroconvulsive therapy (ECT) has been the most potent treatment option for treatment-resistant schizophrenia (TRS). However, the underlying neural mechanisms of ECT in schizophrenia remain largely unclear. This paper examines studies that investigated structural and functional changes after ECT in patients with schizophrenia. Methods We carried out a systematic review with following terms: ‘ECT’, ‘schizophrenia’, and the terms of various neuroimaging modalities. Results Among the 325 records avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 148 publications
1
6
0
Order By: Relevance
“…Previous studies have also pointed out that patients with SZ exhibit decreased nodal local efficiency in the superior frontal gyrus [ 36 ]. It is known that ECT can cause some cognitive side effects [ 40 ]. This may explain the difference in nodal local efficiency of the superior frontal gyrus between SZ patients and healthy controls even after ECT.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also pointed out that patients with SZ exhibit decreased nodal local efficiency in the superior frontal gyrus [ 36 ]. It is known that ECT can cause some cognitive side effects [ 40 ]. This may explain the difference in nodal local efficiency of the superior frontal gyrus between SZ patients and healthy controls even after ECT.…”
Section: Discussionmentioning
confidence: 99%
“…ECT treatment improves the structure and function of the hippocampus and insula in SCZ patients and regulates the function of the prefrontal and thalamic striatum of the default network ( 40 , 41 ). Animal experiments have also shown that ECT attenuates microglia and astrocyte proliferation, thus improving schizophrenic behavior ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous evidence has shown that structural and functional abnormalities in the insula are widely observed in patients with MDD. Meanwhile, an increasing number of MRI studies have also found that structural and functional abnormalities in the insula can be normalized after optimizing treatments, including modified electroconvulsive therapy (mECT) (Dichter et al, 2015 ; Moon et al, 2021 ; Wang, Wei, et al, 2020 ), transcranial magnetic stimulation (Fu et al, 2021 ), transcranial direct current stimulation (Sagliano et al, 2019 ; Sankarasubramanian et al, 2017 ). For example, a recent study found that pretreatment decreased FC with the insula and normalization of this area's function after mECT (Wang, Wei, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%